2000
DOI: 10.1046/j.1365-2524.2000.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the care of patients with depression in primary care: the views of general practitioners

Abstract: Depression is a very common mental illness within the general population and in-patients consulting in general practice. General practitioners are well placed to provide care for patients with mental health problems, as these disorders are often connected with family and social problems, and GPs can provide their patients with long-term follow-up and support. While there are theoretical reasons for the important role of the family doctor, there is limited evidence about how general practitioners view their rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 16 publications
4
33
1
Order By: Relevance
“…Previous qualitative studies have highlighted patients' self-imposed restraint regarding the length of depression consultations, 6 and the importance of GP intuition 7 and tacit knowledge, 8 in influencing clinical decisions in this area, and GPs' preference for treating depression medically despite acknowledging the difficulty of a 'cure'. 9 Where GPs consider patient preferences when contemplating antidepressants, their assessments of patients' attitudes to treatment may differ from patients' self-reported views.…”
Section: Introductionmentioning
confidence: 99%
“…Previous qualitative studies have highlighted patients' self-imposed restraint regarding the length of depression consultations, 6 and the importance of GP intuition 7 and tacit knowledge, 8 in influencing clinical decisions in this area, and GPs' preference for treating depression medically despite acknowledging the difficulty of a 'cure'. 9 Where GPs consider patient preferences when contemplating antidepressants, their assessments of patients' attitudes to treatment may differ from patients' self-reported views.…”
Section: Introductionmentioning
confidence: 99%
“…This appears to be different from GPs' responses to depression in adults, where organisational issues, referral options, therapies, and stigma influence clinical thinking, but not rejection of depression as a valid conceptual category. 21 In our view this aversion to a diagnosis is related, at least in part, to a perceived lack of therapeutic options. Drug treatment is the last therapeutic option for mild and moderate depression in young people, used only when cognitive behaviourial therapy (CBT) has been implemented without response, and even then only initiated by specialists.…”
mentioning
confidence: 98%
“…Chew-Graham et al (2000) and Chew-Graham et al (2002) found that GPs were eager to give patients a diagnosis of depression to provide some comfort in the absence of effective treatments, and diagnosis was seen to have secondary gain for GP and patient in that a diagnosis of depression allowed the patient time off work and provided a clear consultation outcome for the GP. In contrast, in Railton et al (2000), a diagnosis of depression was considered likely to cause stigma with patients not wanting a psychiatric diagnosis in their medical notes. Anticipated resistance to a diagnosis was reported as a barrier to diagnosis and treatment.…”
Section: Detection and Diagnosismentioning
confidence: 99%
“…When discussed, there was a fairly consensual view that guidelines and diagnostic tools did not facilitate diagnosis or treatment for depression. For example, guidelines were seen to categorize depression in unhelpful and not meaningful ways (Railton et al, 2000). Depression was regarded by some GPs as too variable, subjective, or individual to be amenable to guidelines and screening tools (Maxwell, 2005), and these tools were generally considered as unsuitable for use with depressed patients (Lehti et al, 2009;McPherson & Armstrong, 2009):…”
Section: Detection and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation